Implication of islamic finance for Nigeria’s economic diversification through enhanced financial inclusion (2016)
This study empirically investigated the effects of financial inclusion on diversification from the perspective of Islamic finance. The analysis focused on eight Muslim countries with established Islamic financial and banking system, seven Muslim countries with no established Islamic financial and banking system and top eight countries in term of nominal GDP using IMF 2015 data. This provided a comparative analysis of the effects of financial inclusion on diversification in each of these groups of countries. Panel regression technique was used and the Herfindahl concentration index was computed and used to measure the degree of diversification to achieve the study objective. The results revealed, among others, that the economies of the countries with established Islamic financial and banking system were less diversified, as the number of Automated Teller Machines (ATMs) per 10,000km2 increased; but became more diversified as commercial bank branches per 1,000km2 and other deposit takers increased; countries with no established Islamic financial and banking systems became less diversified as the number of commercial bank branches per 1,000km2 increased, while they became more diversified as the number of other deposit takers rose. The study thus recommended, among others, that Nigeria should diversify its finance by utilizing Islamic financial products as viable sources of funding for sectors, such as agriculture, mining, manufacturing, and construction